Edonerpic maleate prevents epileptic seizure during recovery from brain damage by balancing excitatory and inhibitory inputs - Katsuno, Yuki; Jitsuki, Susumu; Ota, Wataru; Yamanoue, Tomomi; Abe, Hiroki; Takahashi, Takuya (Frontiers in Neural Circuits, 2024)
Functional recovery from brain damage, such as stroke, is a plastic process in the brain. The excitatory glutamate α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) plays a crucial role in neuronal functions, and the synaptic trafficking of AMPAR is a fundamental mechanism underlying synaptic plasticity. We recently identified a collapsin response mediator protein 2 (CRMP2)-binding compound, edonerpic maleate, which augments rehabilitative training-dependent functional recovery from brain damage by facilitating experience-driven synaptic delivery of AMPARs. In animals recovering from cryogenic brain injury, a potential compensatory area adjacent to the injured region was observed, where the injection of CNQX, an AMPAR antagonist, significantly attenuated functional recovery. In the compensatory brain area of animals recovering from cryogenic injury, the administration of edonerpic maleate enhanced both excitatory and inhibitory synaptic inputs at pyramidal neurons. In contrast, recovered animals that did not receive the drug exhibited augmentation of only excitatory synaptic input. The threshold of picrotoxin-induced epileptic seizure in recovered animals without edonerpic maleate treatment was lower than in intact animals and recovered animals with edonerpic maleate. Thus, edonerpic maleate enhances motor function recovery from brain damage by balancing excitatory and inhibitory synaptic inputs, which helps prevent epileptic seizures during recovery.